Why digital agripreneurship is rewarding? - Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2018)
Young entrepreneurs from the ACP region explain why agriprenership is attractive and rewarding for them. These include passion, positively impacting the lives of smallholder farmers, creating jobs to employ the growing youth population, among others.